2012
DOI: 10.1007/s10433-012-0249-1
|View full text |Cite
|
Sign up to set email alerts
|

Sense of threat and coping strategies of Israeli older adults during a military operation

Abstract: To examine what levels of sense of threat functionally disabled older people experience during war and the coping strategies they use to protect themselves; to examine factors that explain their sense of threat and coping strategies. A convenience sample that included 138 respondents who were functionally disabled older adults and received homecare services. Face-to-face interviews were conducted using a structured questionnaire. The majority of respondents stayed in their homes during the military operation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 53 publications
1
7
0
Order By: Relevance
“…In contrast, other studies have described a positive coping approach that found Holocaust survivors to be more resilient when confronted with severe stress and mass trauma. Their ability to use previous survival strategies and maintain an optimistic outlook of life helps them adapt to adverse life events (Barel et al, 2010; Lamet & Dyer, 2004; Rozenblat & Iecovich, 2013).…”
Section: Holocaust Survivors and Stressmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, other studies have described a positive coping approach that found Holocaust survivors to be more resilient when confronted with severe stress and mass trauma. Their ability to use previous survival strategies and maintain an optimistic outlook of life helps them adapt to adverse life events (Barel et al, 2010; Lamet & Dyer, 2004; Rozenblat & Iecovich, 2013).…”
Section: Holocaust Survivors and Stressmentioning
confidence: 99%
“…Life‐threatening situations are a significant source of stress for individuals of all ages. This is particularly true of older adults (Näsman et al, 2020; Pourtaghi et al, 2019), who may already be coping with other physical and mental hardships and challenges that come with old age (Rozenblat & Iecovich, 2013). The literature that describes different responses to these stressful situations focuses largely on natural disasters, such as earthquakes, hurricanes, and occasionally wars and terrorist attacks (Lamet & Dyer, 2004; Rozenblat & Iecovich, 2013; Shrira, 2015).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, this subset of the older population was at greater risk of harm due to mobility issues and the often rapid need to take shelter. 21 This interdependent dynamic of emergency circumstances and vulnerable characteristics is highlighted in the literature, recognizing that, in addition to health challenges, older adults are more likely to have logistical and social difficulties such as mobility issues, lack of transportation, and limited social networks. 22 Consequently, researchers have proposed the idea of cumulative risk as a stronger predictor of resilience.…”
Section: Older Adults and Extreme Events Age Alone Does Not Determinementioning
confidence: 99%
“…For example, in the 2006 war between Israel and Lebanon, many homecare workers stayed in their homes, which left the individuals (primarily disabled adults) reliant on them without food, medicine, or care. Consequently, this subset of the older population was at greater risk of harm due to mobility issues and the often rapid need to take shelter 21 . This interdependent dynamic of emergency circumstances and vulnerable characteristics is highlighted in the literature, recognizing that, in addition to health challenges, older adults are more likely to have logistical and social difficulties such as mobility issues, lack of transportation, and limited social networks 22 .…”
Section: Older Adults and Extreme Eventsmentioning
confidence: 99%